ChemInform Abstract: Synthesis of β‐Arylated Alkylamides via Pd‐Catalyzed One‐Pot Installation of a Directing Group and C(sp3)—H Arylation. Issue 33 (July 2016) - Liu, Yunyun; Zhang, Yi; Cao, Xiaoji; Wan, Jie‐Ping
Abstract: The title alkylamides are prepared by one‐pot three‐component condensation of various acyl chlorides, aryl iodides, and aminoquinoline.